DEVELOPMENT AND VALIDATION OF STABILITY INDICATING SIMULTANEOUS UVSPECTROPHOTOMETRIC METHOD FOR DETERMINATION OF EMTRICITABINE, TENOFOVIR DISOPROXIL FUMARATE, COBICISTAT, AND ELVITEGRAVIR IN PURE AND PHARMACEUTICAL DOSAGE FORM - U, Harini; Akm, Pawar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this research work was to develop and validate a simple, precise, and accurate new ultraviolet-spectrophotometric method for the simultaneous estimation of emtricitabine (EMT), tenofovir disoproxil fumarate (TDF), cobicistat (COB), and elvitegravir (ELV) in pure and pharmaceutical marketed dosage form (stribild). Methods: Simultaneous equation method (Vierordt's method) was developed for simultaneous determination of several mixtures containing two or more absorbing drugs (p, q, r, and s) each of which absorbs at the λ max of the other. Forced degradation studies were also conducted, and the drugs were subjected to various stress conditions such as acid hydrolysis, base hydrolysis, oxidative, photolytic, and thermal degradation. Results: The λ max of EMT, ten TDF, COB, and ELV are 283 nm, 259 nm, 240 nm, and 258 nm, respectively. The linearity ranges for the four drugs are EMT (4–24 μg/ml), TDF (10–50 μg/ml), COB (10–120 μg/ml), and ELV (2–10 μg/ml). Conclusion: The Vierordt's method was successfully applied for simultaneous determination of EMT, TDF, COB, and ELV in a mixture of sample solution (pharmaceutical dosage form) and the results obtained were validated and found to be accurate, precise, linear, rugged, and robust.